Intrapreneurial Leadership and Sustainability of Federal Universities in South-South Region Nigeria - Edema, Alfred JM; Abosede A., Usoro (European Scientific Journal, ESJ, 2018)
The study surveys contributions of intrapreneurial leadership to institutional sustainability particularly, federal universities in the south-south region, Nigeria. Institutional leadership and visionary leadership are both consonant to this study. Descriptive statistics and multiple regressions were used in analyzing the data obtained, aided with statistical package for social science. Obviously, federal universities with more academic programmes enjoyed increase in internally generated revenue (IGR) through fee and other charges. There appeared clear indications that universities with some unique programmes are favoured by donators and sponsors. Internally generated revenues by the universities do not necessarily result from so much diversified investments even though those ventures have their revenue contributions. Federal government should inject more funds into infrastructural development in both physical and human forms with more programmes introduced into universities to achieve the objectives, which gave birth to them. The various ventures entered into by the leadership (intrapreneurship) of the universities should be devoid of personal and political sentiments both in the appointment of management teams and financial prudency. Consequently, succeeding administrations should make effort to improve on the vision of inherited venture projects. University managers and administrators should work harder in sourcing for more funds through donors and collaborations while they remain resolutely focused without getting funds diverted.